Resiliensi Komunitas pada Masyarakat Terdampak Erupsi Gunung Merapi - Syaharani, Kharisma; Triyono, Triyono (JURNAL Al-AZHAR INDONESIA SERI HUMANIORA, 2025)
Balerante Village is a disaster-prone area because it is located on the slopes of Mount Merapi in Central Java. This community awareness is a major contribution to the process of community resilience in the village. The purpose of this study is to examine the process of community resilience and the contributions that the community has given to the Balerante Village community. The method in this study uses a qualitative phenomenological approach. Involving 6 people from 3 communities in Balerante Village, with snowball as an informant selection technique. Data collection through participant observation, in-depth interviews and documentation. The data analysis technique uses Interpretative Phenomenological Analysis (IPA) assisted by Atlas.ti software in its coding system. The results of this study show the process of community resilience that occurs, namely cognitive changes and behavioral changes. Cognitive changes in the form of changes in the thinking process from irrational to rational in reading the potential for disasters of the Mount Merapi eruption. Behavioral changes in the form of collaboration between the community and the government regarding disaster control. Then the form of community resilience is empowerment and recovery through the economic sector, the formation of a disaster volunteer community, the existence of disaster response training and simulations, the formation of SSB, strengthening human resources, infrastructure recovery, and completing evacuation preparation equipment. The implications of the research are expected to require more massive mitigation training for the community resilience process in Balerante village.Keywords – Community Resilience, Eruption, Mount Merapi.